2006
DOI: 10.1016/j.ssc.2006.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thermionic emission from electrodeposited Ni–Si Schottky barriers

Abstract: Ni-Si Schottky barriers are fabricated by electrodeposition using n on n+ Si substrates. I -V , C-V and low temperature I -V measurements are presented. A high-quality Schottky barrier with extremely low reverse leakage current is revealed. The results are shown to fit an inhomogeneous barrier model for thermionic emission over a Schottky barrier proposed by Werner and Guttler [J.H. Werner, H.H. Guttler, Barrier inhomogeneities at Schottky contacts, J. Appl. Phys. 69 (3) (1991) 1522-1533]. A mean value of 0.76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 15 publications
2
22
1
Order By: Relevance
“…An explanation can be obtained by taking into account the rapid decrease of the saturation current J s,TFE,r with decreasing temperature suggested in Eq. (9). This effect increases the voltage at which the cross over occurs beyond the range of measurements.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An explanation can be obtained by taking into account the rapid decrease of the saturation current J s,TFE,r with decreasing temperature suggested in Eq. (9). This effect increases the voltage at which the cross over occurs beyond the range of measurements.…”
Section: Resultsmentioning
confidence: 99%
“…This effect increases the voltage at which the cross over occurs beyond the range of measurements. In contrast, electrodeposited Schottky barriers exhibit a spatial distribution of the SB height which results in a decreasing SB height with decreasing temperature [9]. Hence, the TFE saturation current J s,TFE is kept in levels high enough to bring the cross-over and negative temperature coefficient effects within measuring range.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ge-based SB-MOSFETs, however, suffer from increased leakage currents due to its narrow bandgap and low Schottky barrier height [1][2][3]. We have recently shown that Ni-Si diodes prepared by electrodeposition exhibit superior properties to physical vapour deposition [4,5]. In this work, we show that electrodeposited Ni-Ge and NiGe-Ge Schottky diodes on highly doped Ge exhibit near ideal Schottky barrier behaviour with low off current.…”
Section: Introductionmentioning
confidence: 77%